2001
DOI: 10.1103/physrevlett.86.3590
|View full text |Cite
|
Sign up to set email alerts
|

DecoratedAg19on Pt(111) or the “Rare Gas Necklace”

Abstract: Ag19 cluster ions are mass selected and deposited on a Pt(111) surface covered by five monolayers of Kr. Almost monodispersed hexagonal shaped Ag islands are observed after Kr evaporation at 125 K. The identification of the island shape and the exact number of atoms has been successful by decorating the clusters with Kr atoms which can be counted by high resolution scanning tunneling microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 17 publications
(17 reference statements)
1
31
0
Order By: Relevance
“…As has been shown in thorough experimental investigations [19][20][21][22]24], the fragmentation rate of small metal clusters can be reduced to about 10 % by using proper soft landing conditions. From optical absorption and excitation experiments [20,21,24] on clusters soft landed in rare gas matrices it is known that the efficiency of the soft landing process and the fragmentation rate of the clusters depends on the nature of the rare gas matrix.…”
Section: The Soft Landing Processmentioning
confidence: 89%
See 4 more Smart Citations
“…As has been shown in thorough experimental investigations [19][20][21][22]24], the fragmentation rate of small metal clusters can be reduced to about 10 % by using proper soft landing conditions. From optical absorption and excitation experiments [20,21,24] on clusters soft landed in rare gas matrices it is known that the efficiency of the soft landing process and the fragmentation rate of the clusters depends on the nature of the rare gas matrix.…”
Section: The Soft Landing Processmentioning
confidence: 89%
“…STM studies [22] on soft landed clusters also have shown the power of the soft landing technique. Furthermore, they reveal that most of the soft landed clusters form highly symmetric equilibrium structures on the substrate surface.…”
Section: The Soft Landing Processmentioning
confidence: 99%
See 3 more Smart Citations